Meta Analisis Efektivitas Model Pembelajaran Berbasis Masalah terhadap Kemampuan Pemecahan Masalah dan Hasil Belajar Fisika Di SMA - Barus, Anisa Novita; Syah Putra Sembiring, Jantri; Haridsya Aditia, Yuda (Jurusan Teknik Sipil, Politeknik Negeri Ketapang, 2023)
One model recommended for implementing the independent learning curriculum is the problem-based learning model. Problem-based learning is a learning model that prioritizes solving general problems that commonly occur in everyday life. The aim of this research is to determine the effectiveness of using a problem-based learning model in problem-solving abilities and physics learning outcomes in high school. This research uses the Meta Analysis method with data analysis techniques for calculating effect size. The sample used for this research consisted of 20 article items that already had an ISSN. The results of the research that has been carried out can be concluded several things as follows; 1). The average effect size of the problem-based learning model on problem-solving abilities is 1.94. Meanwhile, student learning outcomes were 1.51 which was included in the high category. This means that the application of problem-based learning is effective on student problem-solving abilities and learning outcomes; 2) The most suitable learning material for problem-based learning is Static Fluid material with an effect size of 3.50; 3) Based on the class level that effectively uses the problem-based learning model, namely at the high school class XII level with the high category, the effect size is 1.91.